The main stages of modernization of the People’s Republic of China. (Journal of Oriental Studies, 2016)
The aim of this paper is to investigate a process of modernization of the People’s Republic of China. With the separation the stagesof modernization in China, the author shows the evolution of the process in these countries. The author is also considered the currentmodernization and reforms that are taking place in China.
Keywords: Modernization; procces; the People’s Republic of China; social and economic development